PERMAINAN TEKA-TEKI SILANG DALAM PEMBELAJARAN MEMBACA DAN MENULIS BAHASA ARAB - Ida Latifatul Umroh; Sampiril Taurus Tamaji (Al-Fakkaar, 2022)
An Arabic teacher is a person who has the obligation to introduce, teach, and ensure that students have Arabic language skills. In teaching in the classroom, the Arabic teacher is required to create an effective learning nuance and the material is conveyed and well received by students. Language games are tools / tools used in delivering teaching materials. Language games can also increase students' interest and motivation to learn. This article aims to provide knowledge and insight to Arabic teachers on how to apply / play language games in the form of crossword puzzles in learning to read and write Arabic. The application of the crossword puzzle game is carried out with three stages, namely: the preparation stage, the execution of the game, and the evaluation